Modelos de renovación. El catolicismo social del clero local y de los misioneros extranjeros en el sur andino peruano, 1940-1965 - Fulkerson, S.J., Taylor (Jahrbuch für Geschichte Lateinamerikas, 2025)
The Catholic Church in Cusco, Peru, experienced a pastoral renewal in the decades preceding the Second Vatican Council: the clergy of Cusco, oriented by indigenismo and seeking answers to the question of concentrated landholding and the future of the peasantry, proposed a pro-indigenous pastoral method. At the same time, the Vatican created new structures and missions destined for the abundant clergy of North America, which arrived in the same region with a different model of social Catholicism focused on modernization. This essay proposes to describe and compare the social Catholicisms present in the southern Peruvian Andes between 1940 and 1965. On the basis of archival materials from Peru and the United States, this research seeks the points of agreement and disagreement between the two pastoral styles on the eve of the conciliar reforms.
Keywords: Missionaries; Church Reform; Carmelities; Indigenismo.